ASESMENT POST TRAUMATIC STRESS DISORDER (PTSD) PADA PEREMPUAN KORBAN PERKOSAAN (ACQUAINTANCE RAPE) - Solichah, Mutingatu (Universitas Ahmad Dahlan, 2013)
AbstractThis research was intended to find out whether Post Traumatic Stress Disorder (PTSD) symptom manifested in 5 women acquaintance rape survivors.PTSD Symptom was measured by the Clinician-Administered PTSD Scale (CAPS), a semi structured interview guide that assesses 17 clinical symptoms of PTSD outlines in DSM IV criterion along with 3 associated features of PTSD symptoms. Quantitative data is used todetermine the categorical rating of the PTSD diagnostic status of the participants (PTSD present or absent), symptom severity, and changes gradations of symptom severity over time. Participants were 5 women survivors of acquaintance rape, aged 17 – 35 years old. The results show 4 from 5 participants was diagnosed having PTSD which symptom severity varied. The CAPS’ PTSD diagnostic procedure is combined between the DSM IV defined 20 symptom criteria and its symptom’s frequency and intensity, so the score should range from 20 the lowest up to 160. The participants score range from 35– 125, but one participant was not eligiblefor PTSD diagnostic status due to failure to meet DSM IV criterion for PTSD. The interval time between the traumatic event (rape) and research was ranging from 4 to 31 years, however PTSD symptom’s severity in participants remain high.Keywords: acquaintance rape, Clinician-Administered PTSD Scale (CAPS), DSM IV.